Orientações estratégicas, práticas de gestão da cadeia de suprimentos sustentável e triple bottom line performance: framework conceitual e evidências empíricas - Ottonelli, Janaina (2018)
Companies are increasingly looking for strategic and operational improvements to produce more competitive goods and services. Besides that, they need to balance economic issues with the preservation of the environment and the health and well-being of people. This thesis aims to develop and test a model to identify the relationships between strategic orientations (innovation-led, reputation-led, and efficiency-led), sustainable supply chain management (forward and reverse) and triple bottom line performance (economic, environmental and social). For this, two articles are elaborated. Article I, “A Framework of Strategic Orientations, Sustainable Supply Chain Management Initiatives and Triple Bottom Line Performance”, aims to propose a conceptual framework to verify if there are relations between strategic orientations, practices of sustainable supply chain management and triple bottom line performance. The methodology of this study consists of bibliographic research. The review of the literature allowed the deepening of the subjects covered, as well as identify research gaps to be investigated from the state of the art. The propositions raised indicate that strategic and operational decisions need to consider aspects internal and external to the organization; the strategic guidelines for innovation, reputation and efficiency are antecedents to the adoption of sustainable supply chain management practices; and the adoption of sustainable practices in the forward and reverse supply chain leads to improvements in business performance measured by the economic, environmental and social dimensions. Such propositions led to the development of Article II, “Strategic Orientations, Sustainable Supply Chain Management Initiatives and Triple Bottom Line Performance: empirical evidences from U.S. automotive industry”. It proposition is to develop and test the relationships identified in the conceptual model. The methodology is quantitative research. A research survey instrument was developed and shipped to automotive manufacturing industries in the United States. 210 responses were obtained. The results of the estimation of the integrated model through the modeling of structural equations indicate a significant and negative relationship between the strategic orientation of innovation and the practices of the forward supply chain and the reverse supply chain. Strategic reputation orientation has had a significant and positive relationship with forward supply chain practices and the reverse supply chain. The reverse supply chain presented a significant and positive relationship with environmental and social performance. The novelties of the study were to discuss the strategic orientations of innovation, reputation and efficiency, to consider reverse practices as part of the sustainable supply chain, to measure the triple bottom line performance, especially the social dimension, and to propose a model that integrates strategic issues, operational and performance.